Pengaruh Kedisiplinan Terhadap Hasil Belajar Siswa Kelas II SD Negeri 1 Towangsan - Bella Roes S; Tukiyo Tukiyo; Iswan Riyadi (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2024)
This research is based on the problem of students who are not disciplined before and after learning begins, students are often late for class, do not pay attention to the teacher during the learning process and often make noise in class. The aim of this research is to describe 1) The learning discipline of class II students at SD Negeri 1 Towangsan, 2) The learning outcomes of class II students at SD Negeri 1 Towangsan, 3) The influence of learning discipline on the learning outcomes of class II students at SD Negeri 1 Towangsan, Gantiwarno, Klaten Regency. Lesson 2023/2024. This type of research is quantitative. Data collection techniques use questionnaires and documentation. This research took all members of the class II population of SD Negeri 1 Towangsan, totaling 13 students. Analysis techniques and use validity tests, reliability tests, descriptive statistical analysis, normality tests, linear tests, simple regression tests, and coefficient of determination tests. The results of research using descriptive statistical analysis show that student learning discipline is in the medium category with a percentage of 37% and student learning outcomes are in the medium category with a percentage of 52%. This is proven by the significance value of the simple linear test being smaller than the significance level, namely 0.001 < 0.05 and the calculated t value being greater than the X table, namely 2.706 > 1.796. The coefficient of determination is 0.400, which means that the discipline variable is able to explain 40% of student learning outcome variables, while 60% is influenced by other variables not included in this research.